Exploring the potential of cultural historical activity theory for understanding change in education: lessons from a historical case study of leadership in an Irish school - O’Donoghue, Tom; Neylon, Gerardine (Historia y Memoria de la Educación, 2020)
This paper reports a research project undertaken whose aim was to explore the possibility of using a particular theoretical framework for engaging in preliminary studies aimed at analysing specific historical instances of change in education. The change that was the focus of the investigation was a new school established by the Sisters of Mercy in Ennis, County Clare (Ireland), to replace an original school built in 1865. This was no ‘ordinary school. Instead, it was at the time deemed a model infant and primary school. While the case is of interest in its own right, the principal aim of the study was to explore the potential of cultural activity theory for engaging in historical analyses of cases of its type and using its structure, the CHAT model, as a framework for presenting results.